2017
DOI: 10.1093/jjco/hyx124
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-related pain: a nationwide survey of patients’ treatment modification and satisfaction in Taiwan

Abstract: Although cancer patients were satisfied with their physicians, treatment of cancer pain was still suboptimal. Guidelines should be revised to improve pain assessment and control in patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Patient demographics, cancer characteristics, treatment histories, and current analgesic prescriptions were obtained from medical records. Questionnaires were administered to patients for self-assessment of worst pain intensity over the past 24 hours (scored on a numeric rating scale (NRS), from 0 (no pain) to 10 (worst pain imaginable) [ 10 , 11 ]), sleep disturbance due to cancer pain within the past 7 days, quality of life (assessed using the EuroQol Group 5-Dimension Self-Report Questionnaire 3 Level (EQ-5D-3L) system [ 12 , 13 ]), and patients' satisfaction with pain control status (scored on a 5-point scale: very satisfied, satisfied, acceptable, dissatisfied, and very dissatisfied [ 14 16 ]). Attending physicians assessed their satisfaction with their patients' pain control status (scored on a 5-point scale: very satisfied, satisfied, acceptable, dissatisfied, and very dissatisfied) and adequacy of analgesics for pain control (adequate and not adequate).…”
Section: Methodsmentioning
confidence: 99%
“…Patient demographics, cancer characteristics, treatment histories, and current analgesic prescriptions were obtained from medical records. Questionnaires were administered to patients for self-assessment of worst pain intensity over the past 24 hours (scored on a numeric rating scale (NRS), from 0 (no pain) to 10 (worst pain imaginable) [ 10 , 11 ]), sleep disturbance due to cancer pain within the past 7 days, quality of life (assessed using the EuroQol Group 5-Dimension Self-Report Questionnaire 3 Level (EQ-5D-3L) system [ 12 , 13 ]), and patients' satisfaction with pain control status (scored on a 5-point scale: very satisfied, satisfied, acceptable, dissatisfied, and very dissatisfied [ 14 16 ]). Attending physicians assessed their satisfaction with their patients' pain control status (scored on a 5-point scale: very satisfied, satisfied, acceptable, dissatisfied, and very dissatisfied) and adequacy of analgesics for pain control (adequate and not adequate).…”
Section: Methodsmentioning
confidence: 99%
“…Then, pain reassessment should be performed at speci ed intervals to ensure that analgesic therapy is providing maximum bene t with minimal adverse effects [1] . However, a survey showed that 70% of doctors did not change previously prescribed analgesics based on patients' current pain status [37] . Therefore, the standardization of pain treatment still needs to be strengthened.…”
Section: Discussionmentioning
confidence: 99%
“…Pain severity was signi cantly related with psychological distress among ACPs 33 . Although Taiwanese patients were satis ed with their physicians in terms of pain control, treatment of cancer pain is still suboptimal as more than 70% of physicians do not prescribe analgesics based on their patient's current status 34 . Interestingly, Indonesian patients experienced more pain in this study.…”
Section: Discussionmentioning
confidence: 99%